Multivariable analysis of micro shearing process customized for progressive forming of micro-parts. (April 2015) - Meng, B.; Fu, M.W.; Fu, C.M.; Wang, J.L.
Abstract: With the significantly increasing demand on a large scale of miniaturized parts, the fabrication of micro-parts by directly using sheet metal is proven to be a promising and efficient micro-manufacturing process. In this process chain, shearing is used to pre-pierce hole or blank cylindrical part. In this research, the material deformation behavior and the fracture effect in shearing are extensively studied and it is revealed that they have a significant effect on the subsequent operations and the quality of the fabricated parts. In addition, the influence of forming conditions on deformation behavior, fractured surface quality and dimensional accuracy in shearing operation are systematically investigated. The interactive effects of multi-factors including grain size, lubricated condition and shear velocity on the quality of both the blanked part and the pierced hole are discussed. It is revealed that the forming quality deteriorates with the increase of grain size and shear velocity. High viscosity lubricant leads to low deformation load and small work hardening as well as good surface finish. The rag at the pierced hole edge and the surface breakages on the blanked part exist under high shear velocity, and the shear velocity should be controlled within a certain limit to balance the productivity and surface quality. Furthermore, the ultimate shear strength, billet diameter and burr height have the extreme values when the initial grain size equals to the punch-die clearance. Therefore, the deformation behavior and the product quality in micro shearing process is affected by the interactive effect of material state, die dimension, lubricated condition and shear velocity. Highlights: Interactive effect of multi-factor on the customized micro-shearing process was explored. Hardening accumulation in shearing process was investigated. Effect of different lubricants on deformation behavior and surface finish was analyzed. Surface breakage induced by high shear velocity was discussed.